2000
DOI: 10.1098/rspb.2000.1205
|View full text |Cite
|
Sign up to set email alerts
|

Environmental sex determination in a reptile varies seasonally and with yolk hormones

Abstract: Most hypotheses that have been put forward in order to explain the persistence of environmental sex determination (ESD) in reptiles assume a relatively ¢xed association of sex with temperature-induced phenotype and no maternal in£uence on o¡spring sex. Here we demonstrate the association of maternally derived yolk hormone levels with the o¡spring sex ratio and describe two new aspects of temperaturedependent sex determination (TSD), i.e. seasonal variation in both thermal response and yolk steroid levels. Eggs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
211
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(222 citation statements)
references
References 38 publications
10
211
1
Order By: Relevance
“…Bowden et al (2000) found an overall relation between clutch sex ratio and the ratio of maternal yolk estradiol and testosterone in freshly laid Painted turtle or Red-eared slider turtle eggs, but no direct association between sex of the embryo and hormone concentrations within the individual egg. In these chelonians sex is determined by incubation temperature (Bowden et al, 2001) while birds have genetic sex determination.…”
Section: Sex Differences In Yolk Steroid Levelsmentioning
confidence: 79%
“…Bowden et al (2000) found an overall relation between clutch sex ratio and the ratio of maternal yolk estradiol and testosterone in freshly laid Painted turtle or Red-eared slider turtle eggs, but no direct association between sex of the embryo and hormone concentrations within the individual egg. In these chelonians sex is determined by incubation temperature (Bowden et al, 2001) while birds have genetic sex determination.…”
Section: Sex Differences In Yolk Steroid Levelsmentioning
confidence: 79%
“…Offspring viability is affected not simply by the absolute amount of nutrients allocated to each ovum (Sinervo et al 1992), but also by subtle variations in egg composition. For example, hormone levels in the yolk can modify developmental trajectories (Bowden et al 2000). (ii) Genetic quality of the offspring.…”
Section: (E) Offspring Qualitymentioning
confidence: 99%
“…Recent work has shown that maternal yolk hormones might be involved in sex determination (Janzen et al 1998;Bowden et al 2000;Pike and Petrie 2003) and play an important role in prenatal development (Janzen et al 1998;Eising et al 2001). However, also long-lasting organizing effects of maternal yolk hormones on the progeny have been documented, including effects on postnatal growth, begging intensity, and competitiveness (reviewed in Groothuis et al 2005b andGil 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These opposing costs and benefits indicate that the optimal allocation of maternal yolk androgens into the eggs will depend on current or future environmental or social conditions. Indeed, it is well documented that factors such as breeding density (Schwabl 1997;Reed and Vleck 2001;Groothuis and Schwabl 2002;Mazuc et al 2003;Pilz and Smith 2004), timing of breeding (Schwabl 1996;Bowden et al 2000;Pilz et al 2003;Müller et al 2004), food abundance (Verboven et al 2003;Gasparini et al 2007;Warner et al 2007), partner attractiveness (Gil et al 1999(Gil et al , 2004Tanvez et al 2004;Loyau et al 2007;Kingma et al 2008), or parasitism (Tschirren et al 2004) influence maternal yolk androgen deposition.…”
Section: Introductionmentioning
confidence: 99%